Boron-Doped Graphene Quantum Dots Anchored to Carbon Nanotubes as Noble Metal-Free Electrocatalysts of Uric Acid for a Wearable Sweat Sensor - Wang, Yu-Xuan; Rinawati, Mia; Zhan, Jun-De; Lin, Kuan-Yu; Huang, Chen-Jui; Chen, Kuan-Jung; Mizuguchi, Hitoshi; Jiang, Jyh-Chiang; Hwang, Bing-Joe; Yeh, Min-Hsin (ACS Applied Nano Materials, 2022)
Emerging wearable devices with noninvasive biosensing technologies have sparked substantial interest for constant monitoring of substances in bodily fluids, which might be used to detect human health issues. Uric acid (UA) is a crucial indicator of a high relationship with gout, hyperuricemia, and Lesch–Nyhan syndrome. Therefore, developing a wearable device to noninvasively monitor the UA levels in sweat has drawn enormous attention. In this work, boron-doped graphene quantum dots anchored to carbon nanotubes (BGQDs/CNTs) were proposed as noble-metal-free electrocatalysts for the design of the enzyme-free wearable sensors to monitor the concentration of UA in human sweat. BGQDs could provide extra active sites to enhance the electrocatalytic ability of the UA oxidation reaction. From the results, BGQDs/CNTs exhibit ultrahigh sensitivity of 8.92 ± 0.22 μA μM–1 cm–2 for UA detection compared to pristine CNTs (4.24 ± 0.24 μA μM–1 cm–2). Moreover, density functional theory calculations indicate that B atoms can strengthen the UA molecule adsorption and enlarge electron transfer from the UA molecule to the B-doped graphene sheet, supporting the high sensitivity of BGQDs for UA detection. Hence, this study offers a promising electrocatalyst for using an enzyme-free electrochemical UA sensor with a dependable and steady performance to further the use of wearable electronics.